Macro scale material characterisation in support of meso scale modelling of masonry under uniaxial in-plane loading. (31st January 2020) - Drougkas, Anastasios; Bejarano-Urrego, Leidy; Roy, Nathalie Van; Verstrynge, Els
The amount of detailed experimental data on the mechanical properties of brick masonry in the literature is limited regarding the orthotropic strength and fracture energy. A combined experimental/numerical methodology is proposed for the derivation of the macro scale properties of masonry. The experimental aspect deals with the mechanical characterisation of the individual materials, small masonry samples and masonry wallettes, including the relation of couplet to wallette strength. The numerical aspect is the calculation of the macroscopic properties of the masonry through discrete cracking calculations in two orthogonal directions. The numerical analysis results are compared with the experimental stress-strain results and Digital Image Correlation analysis. The Young's modulus and compressive fracture energy for the masonry composite are derived. The results are analysed in view of the resulting anisotropy of masonry and the obtained failure modes.